Protochondracanthus alatus infesting gills of some marine fish species. - El-Mohsen, A.M.H., M.A. Hassan & H.A.M. Osman, Hussien (Global Veterinaria, 2013)
The distribution of parasitic copepod, Protochondracanthus alatus (Heller, 1865) was investigated in 22 host species, only 2 species, Psettodeserumei and Epinepheluschlorostigma were found susceptible to infestation with parasitic copepods in their gills, with prevalence 29.17% and 25% respectively. The isolated parasitic copepod, P.alatuswas identified by using light and electron microscopes. The infested fishes did not show any clinical abnormalities but the gross pathological lesions were observed in the gill filaments. The overall percent of P. alatus infestation among the infested fish species reached 7.63%. The infestation rates showed seasonal variations, peaked in summer (32.58%), followed by the spring (28.18%), winter (20.54%) and autumn (19.45%). The histopathological alterations showed advanced stages of sever hyperplasia of secondary gill lamellae with infiltration of inflammatory cells, hypertrophy of mucous cells lining epithelial cell layer of secondary gill filaments as well as congestion of branchial blood vessels accompanied with telangiectasis.